Editorial note “Political economy of land reform” - Sousa, M. R.; Filipe, J. (International Journal of Latest Trends in Finance and Economics Sciences, 2016)
This number of the IJLTFES - International Journal of Latest Trends in Finance and Economic Sciences is dedicated specifically to Political Economy of Land Reform. The discussion involving these subjects comprises several authors who have contributed to this number of the Journal with their work and to whom the Editors would like to thank for their participation. After this recognition, it is suitable to thank also to all the reviewers for their contributions for the improvement of the Journal’s issue.